Narcissistic leadership and employees' innovative behaviour: mediating roles of job embeddedness and job engagement. Issue 3 (3rd July 2022) - Norouzinik, Yasaman; Rahimnia, Fariborz; Maharati, Yaghoob; Eslami, Ghasem
ABSTRACT: Organisations need innovation in products and services to grow and survive in competitive environments. Development of innovation in organisations is achieved by human resources.  Employees' innovative behaviour is influenced by various factors, including leadership styles and leaders' characteristics. Therefore, this study aimed to analyse the effect of narcissistic leadership on employees' innovative behaviour by introducing employees' job embeddedness and job engagement as the mediating variables. A narcissistic leader never allows employees to participate in decision-making processes, which affects their corporation's intention and creativity and makes them do what they are expected to do. The data were collected from 455 employees and managers of the governmental organisations located in the eastern provinces of Iran. According to the results, managers' narcissism negatively affected employees' job embeddedness and job engagement. Besides, leaders' narcissism had a negative impact on employees' innovative behaviour. Other research findings indicated the mediating roles of job embeddedness and job engagement. The interaction of leaders' narcissism and leaders' humility is associated with job engagement and job embeddedness. The proposed model provided new insights into the analysis of contradictions in leaders' characteristics. In other words, their characteristics influence employee attitudes, including job embeddedness and job engagement, and employee behaviour and performance.